2017
DOI: 10.1155/2017/9251303
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Effects on Mitochondrial Bioenergetics in Human and Mouse Primary Hepatocytes Follow a Nonlinear Dose Response

Abstract: Arsenite is a known carcinogen and its exposure has been implicated in a variety of noncarcinogenic health concerns. Increased oxidative stress is thought to be the primary cause of arsenite toxicity and the toxic effect is thought to be linear with detrimental effects reported at all concentrations of arsenite. But the paradigm of linear dose response in arsenite toxicity is shifting. In the present study we demonstrate that arsenite effects on mitochondrial respiration in primary hepatocytes follow a nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
(40 reference statements)
3
24
0
Order By: Relevance
“…This is predicted to reduce corresponding protein synthesis, such as to support cytoprotective shifts in bioenergetics and to inhibit apoptosis, respectively, in stressed tumor cells. This was supported by our functional studies, which demonstrated that OCR and ECAR as well as ATP production were significantly reduced in arsenite treated cells, aligning with published data showing that arsenite reduces mitochondrial bioenergetics ( 49 , 50 ). A specific example of a pro-apoptotic factor in this category is BAX (which is also a mitochondrial associated protein).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is predicted to reduce corresponding protein synthesis, such as to support cytoprotective shifts in bioenergetics and to inhibit apoptosis, respectively, in stressed tumor cells. This was supported by our functional studies, which demonstrated that OCR and ECAR as well as ATP production were significantly reduced in arsenite treated cells, aligning with published data showing that arsenite reduces mitochondrial bioenergetics ( 49 , 50 ). A specific example of a pro-apoptotic factor in this category is BAX (which is also a mitochondrial associated protein).…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, as described above, OCR and ATP production were significantly reduced in arsenite treated cells compared to vehicle alone (Figure 2B and D ), supporting the ontology analysis. Moreover, arsenite treatment was previously reported to reduce mitochondrial bioenergetics ( 49 , 50 ). BAX functional studies are included in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…Such a conclusion has already been confirmed by several epidemiological and biological studies [36,53,61]. However, it has been illustrated that several mechanisms of As toxicity, ranging from the generation of oxidative stress, inhibition of DNA repair to modulation of signal transduction pathways and perturbation of DNA methylation patterns, are likely to give rise to nonlinear dose-response relationships, especially at low concentrations [98,99]. Besides, one recent study also revealed a steeper increase at lower As concentrations for fatal CVD [29].…”
Section: Discussionmentioning
confidence: 76%
“…However, whether and how mitochondrial functional capacity is altered in PWS is not known. Thus, we undertook a study using living cells (fibroblasts) from subjects with PWS and healthy controls in order to assess the impact of mitochondrial performance using Agilent Seahorse XF extra-cellular flux technology which allows real-time measurements of several metabolic parameters including cellular substrate utilization, ATP-linked respiration and mitochondrial capacity (Chavan et al, 2017; Tan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%